Clonal spread of carbapenem-resistant Acinetobacter baumannii in a neonatal intensive care unit. Issue 3 (March 2018) - Maciel, W.G.; da Silva, K.E.; Croda, J.; Cayô, R.; Ramos, A.C.; de Sales, R.O.; de Almeida de Souza, G.H.; Bampi, J.V.B.; Limiere, L.C.; Casagrande, J.C.; Gales, A.C.; Simionatto, S.
Summary: Acinetobacter baumannii has often been associated with colonization and/or infection in neonatal intensive care units (NICU). This study describes a clonal spread of carbapenem-resistant A. baumannii (CRAB) isolates in an NICU. In total, 21 CRAB isolates were collected from premature newborns. Only polymyxin B was active against such isolates. Nineteen CRAB isolates were clonally related (Cluster C, which belonged to worldwide-disseminated ST1). All newborns had peripheral access and had received β-lactam therapy previously. The implementation of strict infection control measures was of fundamental importance to eradicate the clonal type in the study hospital.